The Regulation of Adaptation to Cold and Drought Stresses in Poa crymophila Keng Revealed by Integrative Transcriptomics and Metabolomics Analysis - Wang, Yan; Li, Xin-Yu; Li, Cai-Xia; He, Yuan; Hou, Xin-Yi; Ma, Xin-Rong (Frontiers in Plant Science, 2021)
Poa crymophila Keng is highly adaptable to long-term low temperature and drought conditions, making it a desirable foraging grass of the Qinghai-Tibet Plateau. Here, the widely targeted metabolomics and comparative transcriptome analyses were utilized for the discovery of metabolites and genes in P. crymophila in response to cold and drought stresses. P. crymophila were exposed to −5°C for 24 h and recovered to 22°C for 48 h, as well as drought for 10 days followed by re-watering for 1 day. In total, 779 metabolic features were assigned to metabolites and 167,845 unigenes were generated. Seventeen compounds showed significant up-regulation (variable importance in project >1) under both stresses in the metabolic profiling, mainly annotated as carbohydrates, flavones, and phenylpropanoids. The genes which were positively correlated with these metabolites were assigned to pathways (sucrose-starch, raffinose, phenylpropanoid, and flavone metabolism) using the Mapman software package. Alpha-amylase, beta-fructofuranosidase, and sugar transport genes degraded the glucose and starch to small molecule sugars for the purpose of osmotic adjustment and to provide more energy for the growth of P. crymophila in an adverse environment. The induction of cinnamoyl-CoA reductase (CCR) and the MYB gene as well as the sharp increase in schizandrin, a kind of lignan, showed that this likely has the closest connection with the tolerance to both stresses. Four significantly induced flavone compounds are probably involved in reducing oxidative damage. Our results indicated that activation of the phenlypropanoid pathway plays the primary role in P. crymophila adapting to harsh environments. This study showed the mechanism of P. crymophila responding to both cold and drought stresses and showed the discovery of a new biological regulator against stresses.